2022
DOI: 10.3389/fenvs.2022.915531
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability of surface air pollutants in megacities of South Korea

Abstract: This study investigated the various temporal (weekly, monthly, and inter-annual) variability of air pollutants (PM10, SO2, NO2, O3, CO) in seven megacities in South Korea (Seoul, Busan, Incheon, Daegu, Gwangju, Daejeon, and Ulsan). We found that the general decreasing trend of PM10, SO2, NO2, and CO. An exceptional pollutant is O3, showing a clear increasing trend consistently in all seven megacities. Seasonally PM10, SO2, NO2, and CO have the highest level in winter due to the large fossil-fuel combustion for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 71 publications
2
8
0
Order By: Relevance
“…This study is not purely statistical in nature because it also takes into account the DAQx* concentration ranges of air pollutants. Thus, it supplements previous statistical studies on characteristics of air pollutants in Seoul [6,14,[37][38][39], which are primarily related to annual trends, daily cycles of hourly means, weekly cycles of daily means, and annual cycles of monthly means but not to daily maximum 1 h means. Moreover, they do not sufficiently account for the differences between and within AQMS types.…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…This study is not purely statistical in nature because it also takes into account the DAQx* concentration ranges of air pollutants. Thus, it supplements previous statistical studies on characteristics of air pollutants in Seoul [6,14,[37][38][39], which are primarily related to annual trends, daily cycles of hourly means, weekly cycles of daily means, and annual cycles of monthly means but not to daily maximum 1 h means. Moreover, they do not sufficiently account for the differences between and within AQMS types.…”
Section: Introductionsupporting
confidence: 67%
“…Seoul is the capital of the Republic of Korea, has a population of approximately 11 million (as of November 2022), an area of approximately 605 km 2 [29,40], and a relatively high level of air pollution [6,14,37,43], which was also confirmed by the DAQx* results in [36]. This is one of the main reasons for the relatively high density of AQMSs operated by the Korea Environment Cooperation in Seoul [44].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ambient concentrations of PM 2.5 , SO 2 , and NO x in Northeast Asia have declined recently (Ali et al, 2023;Bae et al, 2023;Lee et al, 2022;Zhai et al, 2021). Previous studies reported that this downward trend resulted from emission reductions by strict emission control policies and social issues such as the COVID-19 pandemic (Bae et al, 2021;Hasnain et al, 2023;Yao et al, 2023;Zhang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%